PENGARUH PELATIHAN KERJA TERHADAP KINERJA SATUAN PENGAMANAN (SATPAM) DI KPP PRATAMA PALU - Muhammad Rakha Ishlah Adimad; Laisa Liza (Jurnal Ekonomi Trend, 2023)
Human Resources (HR) is an important component in an institution. The Security Unit (SATPAM) is an integral part of human resources as a security unit within an institution. In carrying out their duties as the development of limited police functions, security guards play the role of: Supporting elements for the leadership of organizations, companies and/or government agencies/institutions, and provide security and order in the environment/workplace. Development and training of security guards must be carried out in order to improve the competence and quality of security guards hence creating a safe office environment. The background of this study is that increased training plays an important role in improving the performance of Satpam. Location The research was conducted at Palu Tax Office, with the unit of analysis used in this study is the individual (Satpam). Data collection was carried out through interviews. The data analysis technique uses Simple Linear Regression, namely the relationship between the Independent Variable (X), namely the Frequency of training and the Dependent Variable (Y), namely the Performance of the KPP Pratama Palu Security Unit. The number of respondents is as many as 11 people. The results of the study show that the training has a significant effect on the Satpam Performance. 95.4% of the security guard's performance variable at KPP Pratama Palu is influenced by the training variable. The frequency of training held by KPP Pratama Palu affects the performance of the Security Unit (Satpam) KPP Pratama Palu. Keywords : Training, Security Unit, Performance, KPP Pratama Palu